2006
DOI: 10.1128/cvi.00144-06
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Evaluation of a Synthetic Oligosaccharide-Protein Conjugate Vaccine against Haemophilus influenzae Type b in Human Adult Volunteers

Abstract: Since 1989, we have been involved in the development of a vaccine against Haemophilus influenzae type b. The new vaccine is based on the conjugation of synthetic oligosaccharides to tetanus toxoid. Our main goals have been (i) to verify the feasibility of using the synthetic antigen and (ii) to search for new production alternatives for this important infant vaccine. Overall, eight trials have already been conducted with adults, children (4 to 5 years old), and infants. We have described herein the details fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…The utility of certain maleimide (but not hydrazido) containing linkers is supported by the fact that commercial vaccines have been produced utilising similar maleimide linkers as in this study, though without the hydrazido functionality, such as the synthetic Haemophilus influenzae capsular polysaccharide serotype B vaccine, developed by Cuban scientists [12]. An immune response to the maleimide functionality could be anticipated with the Cuban vaccine if indeed the maleimide functionality was immunodominant, although this has not been reported, and the Cuban vaccine has proven to have an excellent safety profile and provokes Haemophilus influenzae serotype B specific antibody responses similar to the non-synthetic carbohydrate containing vaccine [13]. A potentially critical issue in understanding the lack of bactericidal activity of rabbit sera to wild-type meningococci, concerns the importance of the presentation of the different terminal LPS sugar structures that are characteristic of the mutants used in the candidate vaccine immunogens.…”
Section: Resultsmentioning
confidence: 75%
“…The utility of certain maleimide (but not hydrazido) containing linkers is supported by the fact that commercial vaccines have been produced utilising similar maleimide linkers as in this study, though without the hydrazido functionality, such as the synthetic Haemophilus influenzae capsular polysaccharide serotype B vaccine, developed by Cuban scientists [12]. An immune response to the maleimide functionality could be anticipated with the Cuban vaccine if indeed the maleimide functionality was immunodominant, although this has not been reported, and the Cuban vaccine has proven to have an excellent safety profile and provokes Haemophilus influenzae serotype B specific antibody responses similar to the non-synthetic carbohydrate containing vaccine [13]. A potentially critical issue in understanding the lack of bactericidal activity of rabbit sera to wild-type meningococci, concerns the importance of the presentation of the different terminal LPS sugar structures that are characteristic of the mutants used in the candidate vaccine immunogens.…”
Section: Resultsmentioning
confidence: 75%
“…The utility of certain maleimide (but not hydrazido) containing linkers is supported by the fact that commercial vaccines have been produced utilising similar maleimide linkers as in this study, though without the hydrazido functionality, such as the synthetic H. influenzae capsular polysaccharide serotype B vaccine, developed by Cuban scientists [35]. An immune response to the maleimide functionality could be anticipated with the Cuban vaccine if indeed the maleimide functionality was immunodominant, although this has not been reported, and the Cuban vaccine has proven to have an excellent safety profile and provokes H. influenzae serotype B specific antibody responses similar to the non-synthetic carbohydrate containing vaccine [36]. In this study although a large proportion of the immune response was apparently distracted to the maleimide/hydrazide linker, we still obtained functional antibodies as serum bactericidal assays revealed that post-immune sera were capable of killing wild-type M. catarrhalis cells at dilutions approaching 1:50 when compared to the appropriate controls and pre-immune sera.…”
Section: Discussionmentioning
confidence: 90%
“…Chemical conjugation is widely used to make peptides and polysaccharides immunogenic [32][33][34][35], and also used to enhance immunogenicities of some protein antigens [27,36,37]. Although frequently used carrier proteins such as bacterial detoxified exotoxins or nontoxic exotoxin mutants as well as some bacterial outer membrane protein complexes have shown to be effective and safe in humans, their preparation is often difficult or access to them is often limited.…”
Section: Discussionmentioning
confidence: 99%